VARIASI STRAIN DI SEKITAR SESAR BARIBIS BERDASARKAN DATA PENGAMATAN GPS KONTINYU (2016-2018) - Ridho Ilahi (Elipsoida : Jurnal Geodesi dan Geomatika, 2019)
Java island is one of big island with a high geodynamic condition, which in the southern part of Java Island occur subduction between Sunda Block and Indo-Australian Plate. The subduction zone forms a regional geological pattern in the maindland of Java which can be seen as fault pattern. Baribis fault is one of the active fault in the west Java, which consist west and east segment. The west segment called by inferred fault, while the east segment called by fix fault. This paper discusses about the strain variation along Baribis fault based on GNSS data, that used to see the geodynamic behavior between Indo-Australian plate and the Sunda block.The velocity and the coordinates of observation point is calculated using weight least square method in the GAMIT and GLOBK 10.7 software, while the principle strain rate calculated using least square collocation method in GeoStrain software. The result show compression happen in the northern part of Banten province, western part of DKI Jakarta and western part of West Java province. Meanwhile the extension happened in eastern part of  DKI Jakarta till the southern part of DKI Jakarta.